2022
DOI: 10.1177/20412479221107469
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery systems based on renewable polymers: A conceptual short review

Abstract: There are ever increasing concerns about environmental and health hazards of conventional synthetic polymers. These polymers are not sustainable because their production process relies on fossil-based feedstocks and energy sources. Economic benefits and beneficial physicochemical and mechanical properties have made synthetic polymers to be used in wide range of applications from packaging to biomedicine. On the other hand, modern chemistry has provided us with invaluable tools to make well-defined polymers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Hydrogels have been extensively used for biomedical applications such as drug delivery, wound dressing, and tissue engineering. [45][46][47] For example, an injectable thermosensitive hydrogel based on poly(N-isopropylacrylamide) (PNIPAM) and gelatin, embedded with cell encapsulated alginate microgels, was used as bioactive wound dressing. 48 Alginate microgels containing stem cells were crosslinked using ionic interactions physically.…”
Section: Biomedicinementioning
confidence: 99%
“…Hydrogels have been extensively used for biomedical applications such as drug delivery, wound dressing, and tissue engineering. [45][46][47] For example, an injectable thermosensitive hydrogel based on poly(N-isopropylacrylamide) (PNIPAM) and gelatin, embedded with cell encapsulated alginate microgels, was used as bioactive wound dressing. 48 Alginate microgels containing stem cells were crosslinked using ionic interactions physically.…”
Section: Biomedicinementioning
confidence: 99%
“…8 Microorganisms are also capable of producing polymer materials, with recent advancements in the field of synthetic biology and metabolic glycoengineering producing artificial microorganisms that produce specialised types of biopolymers. [9][10][11][12] Natural SAPs, particularly polysaccharides, are sought after due to their non-toxicity, biocompatibility, and biodegradability. 5 In a study on the enhancement of soil quality using natural and synthetic polymers Abd El-Hafez et al (2019) found that the natural polymers enhanced soil physical and hydro-physical properties, whilst synthetic treatments reduced the same parameters leading to the reduced growth of lettuce plants.…”
Section: Introductionmentioning
confidence: 99%
“…12 The limited degradability of packaging produced from non-biodegradable polymers when discarded in nature, associated with the high levels of production of synthetic polymers, made the industry and the academic community interested in the development of ecological, biodegradable and sustainable materials. [13][14][15][16] The researchers highlighted the great potential of raw materials from natural sources, such as starch, cellulose and their derivatives, which can be used in the development of films applied to food packaging and edible coatings. [17][18][19] In 2019, the production of biopolymers was estimated at around 2.11 million tons, with a forecast that in 2024 around 2.43 million tons will be produced, of which approximately 70% (1.2 million tons) are applied in the packaging sector.…”
Section: Introductionmentioning
confidence: 99%